ELECTRICAL SIGNS OF IMPULSE CONDUCTION IN SPINAL MOTONEURONS - Lloyd, David P. C. (The Rockefeller University Press, 1951)
An analysis has been made of the electrical responses recorded on the surface and within the substance of the first sacral spinal segment when the contained motoneurons are excited by single and repeated antidromic ventral root volleys. A succession of negative deflections, designated in order of increasing latency m, i, b, d, has been found. Each of those deflections possesses some physiological property or properties to distinguish it from the remainder. Indicated by that fact is the conclusion that the successive deflections represent impulse conduction through successive parts of the motoneurons that differ in behavior, each from the others. Since the spinal cord constitutes a volume conductor the negative deflections are anteceded by a positive deflection at all points except that at which the axonal impulses first enter from the ventral root into the spinal cord. Frequently two or more negative deflections are recorded together in overlapping sequence, but for each deflection a region can be found in which the onset of that deflection marks the transition from prodromal positivity to negativity. Deflection m is characteristic of axonal spikes. Latent period is in keeping with known axonal conduction velocity. Refractory period is brief. The response represented by m is highly resistant to asphyxia. Maximal along the line of ventral root attachment and attenuating sharply therefrom, deflection m can be attributed only to axonal impulse conduction. Deflection i is encountered only within the cord, and is always associated with a deflection b. The i,b complex is recordable at loci immediately dorsal to regions from which m is recorded, and immediately ventral to points from which b is recorded in isolation from i. Except for its great sensitivity to asphyxia, deflection i has properties in common with those of m, but very different from those of b or d. To judge by properties i represents continuing axonal impulse conduction into a region, however, that is readily depolarized by asphyxia. Deflection b possesses a unique configuration in that the ascending limb is sloped progressively to the right indicating a sharp decrease in velocity of the antidromic impulses penetrating the b segment. A second antidromic volley will not conduct from i segment to b segment of the motoneurons unless separated from the first by nearly 1 msec. longer than is necessary for restimulation of axons. This value accords with somatic refractoriness determined by other means. Together with spatial considerations, the fact suggests that b represents antidromic invasion of cell bodies. Deflection d is ubiquitous, but in recordings from regions dorsal and lateral to the ventral horn, wherein an electrode is close to dendrites, but remote from other segments of motoneurons, d is the initial negative deflection. In latency d is variable to a degree that demands that it represent slow conduction through rather elongated structures. When associated with deflection b, deflection d may arise from the peak of b with the only notable discontinuity provided by the characteristically sloped rising phase of b. Deflection d records the occupation by antidromic impulses of the dendrites. Once dendrites have conducted a volley they will not again do so fully for some 120 msec. Embracing the several deflections, recorded impulse negativity in the motoneurons may endure for nearly 5 msec. When the axonal deflection m is recorded with minimal interference from somatic currents, it is followed by a reversal of sign to positivity that endures as long as impulse negativity can be traced elsewhere, demonstrating the existence of current flow from axons to somata as the latter are occupied by impulses. Note is taken of the fact that impulse conduction through motoneurons is followed by an interval, measurable to some 120 msec., during which after-currents flow. These currents denote the existence in parts of the intramedullary motoneurons of after-potentials the courses of which must differ in different parts of the neurons, otherwise nothing would be recorded. The location of sources and sinks is such as to indicate that a major fraction of the current flows between axons and somata. For approximately 45 msec. the direction of flow is from dendrites to axons. Thereafter, and for the remaining measurable duration, flow is from axons to dendrites.